The equilibrium gap method - Syed Muhammad, Kashif (IIUM Press, 2011)
This chapter discusses the equilibrium gap method that utilizes full field data measured over a surface. The method has been shown to give promising results for identification of elastic constitutive properties. Also, the method has been applied to the case of a damaged specimen. Initial trial values of unknown data is given as input and then the gap between actual and numerical result is reduced.